Analysis of the Utilization Policy of Wrocław Yacht Harbors, Marinas and River Ports - Adamiczka, Hanna (Analiza polityki wykorzystania wrocławskich przystani jachtowych, marin i portów rzecznych, 2023)
The development of yacht harbours in Wrocław is a significant element of European transport policy, linked to maintaining mobility with minimal environmental impact. The increasing popularity of recreational navigation and the development of a port infrastructure reflect societal awareness and new expectations related to leisure. The Oder, the second longest river in Poland, serves as a navigable route, and the Wrocław Water Node constitutes a unique 45 km-long system. The research aimed to present Wrocław's spatial policy regarding yacht ports and marinas. The analysis of the major ports highlights the diversity of their condition while maintaining their port functions within local plans. Planned investments include new moorings, marinas, parking spaces, restaurants, green areas, and tourist infrastructure. These ports were also analysed based on Wrocław's ownership structure. The study employed various methods, including literature analysis, primary documents, legal acts, cartographic materials, field research, and in-depth interviews.
Biblioteka Regionalisty = Regional Journal, 2023, Nr 23, s. 1-10
Keywords: yacht harbour; marina; river; Wroclaw; spatial planning; port jachtowy; rzeka; Wrocław; planowanie przestrzenne